COMPETENCY DEVELOPMENT STRATEGY FOR MADRASAH TEACHERS IN DELI SERDANG REGENCY IN IMPLEMENTING THE INDEPENDENT CURRICULUM - Panjaitan, Hendripal; Yusuf, Muhammad; Siahaan, Amiruddin; Nurhasanah, Siti (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze madrasah teachers' readiness and competence level in implementing the Merdeka Curriculum, identify challenges, and formulate effective strategies to improve teacher competence in the Deli Serdang Regency. This research employed a qualitative approach with a case study method. Data collection techniques included in-depth interviews, observations, and documentation studies, while data were analyzed thematically through data reduction, data presentation, and conclusion drawing. The study results indicate that most madrasah teachers are not yet fully prepared to implement the Merdeka Curriculum due to limited conceptual understanding, insufficient training, and a lack of supporting facilities. Challenges include low digital literacy, limited mentoring, and restricted access to learning resources. Strategies that can be applied include practice-based training, intensive mentoring, the use of technology, strengthening professional learning communities, and supportive policies from school leaders and related institutions. This study recommends the need for synergy among madrasahs, the government, and educational communities to create a supportive learning ecosystem for the optimal implementation of the Merdeka Curriculum.